The Relationship between Perfectionism and Rumination in Post Traumatic Stress Disorder - Egan, Sarah; Hattaway, M.; Kane, Robert (Cambridge University Press, 2014)
Background: To date no research has investigated the link between Post Traumatic Stress Disorder (PTSD) and perfectionism in a clinical sample. Aims: The aim of the current study was to examine whether there is a relationship between PTSD and perfectionism. This is important to address as many studies have demonstrated a link between other anxiety disorders, eating disorders, depression and perfectionism. The research also aimed to examine whether rumination was a mediator of the relationship between PTSD and perfectionism. Method: The sample consisted of 30 participants who were currently in treatment for PTSD. Results: The results suggest that perfectionism and PTSD symptoms were significantly correlated. In addition, rumination was a significant mediator of the relationship between Concern over Mistakes and PTSD. Conclusions: These findings help increase understanding about the relationships of perfectionism and rumination in PTSD and have implications for the treatment of PTSD.